Analisis Harga Pokok Penjualan Dan Laba : Studi Kasus Di UD Han Petshop Lamongan Tahun 2023 - Gadis Kusuma Ningrum; Abu Darim (FEB Universitas Maritim Semarang, 2023)
This research aims to analyze the calculation of cost of goods sold and profit determination at UD Han Petshop Lamongan. The approach used in this research is a case study in accordance with the problem formulation and research objectives. The data collection techniques used were observation, interviews and documentation. The data analysis techniques in this research are data collection, data reduction, data presentation, and drawing conclusions, using data validity techniques used, namely source triangulation and method triangulation. The results of this research show that UD Han Petshop Lamongan in calculating the cost of goods sold has complied with the calculation procedure by entering initial inventory data plus net purchases then minus ending inventory. In determining profit, the company has included all the data required in the profit and loss financial report. The data used in determining net profit before tax is net sales minus the cost of goods sold and operating costs.